Образы женщин в рекламе - Малицкая, H. A.; Бунецкая, Е. А. (ХНУРЕ, 2019)
While the power ol advertisements has long been known, investigations of sociocultural influences on sexual attitudes have been limited primarily to studies of sexually aggressive media. In this publication we examined the effects on sexual attitudes of different portrayals of women in advertisements.